Hubungan Akal Dan Wahyu Menurut Teolog Muslim - Yudi Kuswandi (ISLAMICA, 2015)
Tersetting sense to describe the nature of truth. He can tell the difference deeds good and bad, love and hate, lies and truth, falsehood and of truth. In human nature also has drawbacks, such as weakness in abstinence so gullible power, like a hasty, inaccurate, and so forth. Then this is where the urgency of Revelation is guiding sense to the truth, because people will not know the true nature except berpondasi on revelation. IbnTaymiyya and IbnHazm's position as an instrument Intellect condition or disposition "gharizah". Gharizah sense will be a requirement for all kinds of science, whether Rational or Irrational, so that sense can not be contrary to revelation. Muslim philosophers who sought to prove the relationship between reason and revelation of which IbnRushd which explains the "relationship". IbnTaymiyya tried to avoid conflict or explain "suitability".